Designing Needs-Based Arabic Learning Modules for First-Year Students at STIT Pringsewu - Supriyanti, Ika; Aulia, Maya (LinguaScopes: International Journal of Language Education, 2025)
This study investigates the design of a needs-based Arabic learning module for first-year students at STIT Pringsewu through a descriptive qualitative case study approach. Using in-depth interviews, classroom observations, and document analysis, key student themes emerged, such as high anxiety in speaking, reliance on the mother tongue for grammar, and a marked preference for multimedia input. Lecturer perspectives highlighted the importance of nahw mastery, time constraints, and student motivation. Analysis revealed gaps between curriculum intentions and classroom practice. The resulting conceptual module directly addresses these needs by integrating video dialogues, scaffolded grammar exercises, and affective support strategies. Expert review further refined the module to fit the cultural and instructional context of STIT Pringsewu. This research contributes a robust framework for curriculum improvement and suggests future studies to develop and test the module in real classrooms.